MOLECULAR CHARACTERIZATION OF CARBAPENEM RESISTANT Klebsiella pneumoniae FROM WOUND SURFACES OF PATIENTS ATTENDING GENERAL HOSPITAL MINNA, NIGERIA - Doko, Hafsat Isa; Enejiyon, Sherifat Ozavize; Wuna, Muhammad Muhammad; Adedeji, Saheed Abdulameen; Sa’adu, Murtala; Fasasi, Rukayat Abidemi; Adabara, Nasiru Usman (FUDMA JOURNAL OF SCIENCES, 2024)
The spread of carbapenem-resistant bacteria constitutes a global public healthcare problem due to their rate of spread and limited therapeutic options against them. The purpose of this study was to isolate and characterize carbapenem-resistant Klebsiella pneumoniae (CRKP) from patient wound surfaces at General Hospital Minna, Nigeria. One hundred wound specimens were obtained and screened for K. pneumoniae. Using the Kirby-Bauer disk diffusion technique, isolates of K. pneumoniae were tested for carbapenem resistance using imipenem and meropenem discs. Carbapenem-resistant K. pneumoniae were screened for carbapenemase production using a modified carbapenem-inactivation method. Using polymerase chain reaction, carbapenemase-encoding genes were also tested for in carbapenem-resistant isolates. Results revealed that 63.0% of the samples were bacteria culture positive and 67 Gram negative bacteria including; Klebsiella pneumoniae 14(20.9%), Escherichia coli 33 (49.2%) and Pseudomonas aeruginosa 20 (29.9%) were isolated. Infection rate was higher in females (52.2%) than males and in patients within the age group of 21-40 years (49.3%). Nine out of the 14 Klebsiella pneumoniae isolates were resistant to carbapenems, and they exhibited high-level of resistance to Trimethoprime-sulfamethoxazole, Ciprofloxacin and Amoxicillin+clavulanate and high level of susceptibility to Fosfomycin and Colistin. None of the CRKP produced carbapenemase production and 55.6% were indeterminate. Molecular identification also confirmed that genes encoding carbapenem resistance (blaOXA-48, blaKPC and blaNDM) were not present in the five indeterminate, carbapenem resistance Klebsiella pneumoniae isolates. High prevalence of CRKP was recorded in the study area and efforts should be intensify towards limiting their spread.